Pengaruh Pemberian Vitamin C Topikal terhadap Sekresi Melanin - Michelle C. J. M. Loho; Elvin C. Angmalisang; Sonny J. R. Kalangi (eBiomedik, 2022)
Abstract: One of the cosmetic products that are widely used in skin care is topical vitamin C because it is believed to help in reducing hyperpigmentation of the skin by inhibiting the melanin secretion pathway. This study aims to determine the effects of topical vitamin C on melanin secretion. The study was conducted using a literature review method and the literature was taken from 1 database, Pubmed. The keywords used were topical AND vitamin c OR ascorbic acid AND skin pigmentation OR depigmentation OR antipigmentation OR melanin pigmentation OR melanin synthesis OR melanin index OR melanin. The article search used the PICOS framework, and obtained 10 literatures. In the study, it was found that vitamin C had an effect on melanin secretion. Vitamin C works by inhibiting the tyrosinase enzyme which affects the initial process of melanin secretion. In conclusion, topical vitamin C has an effect on melanin secretion.Keywords: melanin; melanogenesis; vitamin CÂ Abstrak: Salah satu produk kosmetik yang banyak digunakan dalam perawatan kulit merupakan vitamin C topikal karena dipercaya dapat membantu dalam mengurangi hiperpigmentasi pada kulit dengan bekerja pada sekresi melanin. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian vitamin C topikal terhadap sekresi melanin. Penelitian dilakukan dengan metode literature review dan literatur diambil dari 1 database, Pubmed. Kata kunci yang digunakan adalah topical AND vitamin c OR ascorbic acid AND skin pigmentation OR depigmentation OR antipigmentation OR melanin pigmentation OR melanin synthesis OR melanin index OR melanin. Pencarian artikel digunakan PICOS framework, dan didapatkan 10 literatur. Pada penelitian didapatkan bahwa vitamin C memiliki pengaruh terhadap sekresi melanin. Vitamin C bekerja dengan cara menginhibisi enzim tirosinase yang berpengaruh pada proses awal sekresi melanin. Sebagai simpulan, vitamin C topikal berpengaruh pada sekresi melanin.Kata kunci: melanin; melanogenesis; vitamin C